Hyperemesis Gravidarum and Maternal Age under 20 Years: A Cross Sectional Study - Munawaroh, Siti; Pratiwi, Laurita Laras; Soetrisno, Soetrisno (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2022)
Background: Nausea and vomiting during pregnancy are common. When this happens excessively and interferes with activities, it is also called hyperemesis gravidarum. This situation can be detrimental to the mother and fetus, such as nutritional deficiencies, dehydration, electrolyte disturbances, weight loss during pregnancy, and an increased risk of childbirth, premature birth, and low birth weight. Many factors can cause the occurrence of hyperemesis gravidarum, one of which is the age of the mother under 20 years. This study aims to determine the relationship between hyperemesis gravidarum with maternal age under 20 years.Method: a cross-sectional study with a fixed disease sampling method. Subjects were divided into two groups, there were 50 pregnant women with hyperemesis gravidarum and 50 pregnant women without hyperemesis gravidarum. This research was conducted in Dr. Moewardi Hospital, Surakarta. The independent variable being the mother's age under 20 years old and the dependent variable being hyperemesis gravidarum. The Fisher's Exact test was used to evaluate the data in SPSS. The participants in this study were 100 pregnant women,Result:12 of whom were under 20 and 88 of whom were between 20 and 35. The Fischer's Exact test yielded a p-value of 0.03, indicating that maternal age < 20 was related to hyperemesis gravidarum. Hyperemesis gravidarum is more common and has a higher risk in pregnant women under the age of 20.Conclusion: There is a link between maternal age and the occurrence of hyperemesis gravidarum among women under the age of 20.